Successfully transitioning a research project to a commercial spin‐out using an agile software process. Issue 5 (12th July 2013) - Dowling, Phelim; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract The ultimate success of any research activity is to see it bears fruit in terms of real life use and commercial success. A key element in driving a good concept or idea through the various research and development stages and into full commercial use is the software process that supports it. In the early days of its evolvement, the product will require less in terms of unit test coverage and automated test packages and more in the way of room to research and discover the innovation that will make the product unique and of high value. However, as the project progresses and a horizon appears with capital investors and large customer bases, the supporting software process needs to adapt fluidly to these evolving requirements. Efficient use of resources, shorter release cycles and better levels of quality coverage are a necessity to meet stakeholder demands for new features, better features and all to be delivered more quickly. This paper examines the successful transition of a research project to a fully fledged commercial entity with an emphasis on the software process and quality methodologies used. Copyright © 2013 John Wiley & Sons, Ltd.